2016
DOI: 10.2485/jhtb.25.205
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Human Gingival Epithelial Cells on Titanium Following Abrasion of the Adjunctive Glycine Air Polishing Powder

Abstract: Treatment to replace missing teeth with implants has been available for nearly 50 years. However, many implants are subject to peri-implantitis because of resorption of the bone supporting the implant. Therefore periodontal maintenance to avoid bacterial infection around an implant device is essential. There are several methods of maintenance available to remove bacterial infections. One of these methods involves the direct removal of bacterial infection in the implant sulcus using tooth surface abrasives. Abr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…After reading the full‐text articles, 10 articles were excluded: three articles due to using the AA in combination with other decontamination methods, one study was not about titanium surface, two articles did not use AA for decontamination, one study was not in English and not published in a peer‐review journal, one study used the AA powder in an antimicrobial solution but did not use the AA device, one study had an in vivo design with decontamination procedures taking place in the beagle dogs, and the full text for one study was not retrieved . The 48 included articles were ultimately processed for data extraction . The summary of the search strategy is depicted in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After reading the full‐text articles, 10 articles were excluded: three articles due to using the AA in combination with other decontamination methods, one study was not about titanium surface, two articles did not use AA for decontamination, one study was not in English and not published in a peer‐review journal, one study used the AA powder in an antimicrobial solution but did not use the AA device, one study had an in vivo design with decontamination procedures taking place in the beagle dogs, and the full text for one study was not retrieved . The 48 included articles were ultimately processed for data extraction . The summary of the search strategy is depicted in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the SEM results, except for three studies that reported no surface change, other studies showed some level of morphological changes which were different in nature and intensity based on the surface modification and powder type. Regarding the surface topology, 2 studies showed that the Ra value for SB was higher than glycine and untreated controls while another study found no difference . Six articles reported on surface composition using energy dispersive‐x spectrometry (EDS) from which except for one study, others found powder remnants and changes in surface composition related to the application of AA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because it appears safe to use on implant surfaces, glycine powder treatments could play a role in the management of PIM. 77,80,193 The present study showed particle residues of calcium carbonate and sodium bicarbonate on some of the treated surfaces. This is consistent with previous work which showed sodium bicarbonate particles left on SLA surfaces.…”
Section: Discussionsupporting
confidence: 51%
“…should not modify dramatically the original surface, 80,81 despite causing 'rounding' of rough peaks on the surface. Such rounding effects are likely when the particles used are calcium phosphate or hydroxyapatite.…”
Section: Cavitation-based Approachesmentioning
confidence: 99%